Evaluasi dan Perencanaan Angkutan Sekolah di Kabupaten Gianyar - Dewa Ayu Trisna Adhiswari Wedagama; Ni Putu Delima Yogeswari Saraswati; Luh Putu Egarustari (Publikasi Indonesia, 2023)
Gianyar got the position of fifth rank from all regencys in Bali Province as the highest number of schools, it has 382 schools. The highest number of schools in one region can make traffic density so it will cause congestion or crowded, because road capacity is inadequate. To overcome this problem, the Gianyar District Transportation Office held a free school transport program in the form of the Trans Harmoni Bus which has been operating since 2016 and Trans Gianyar transportation which was inaugurated on October 19, 2018. This research aims to evaluate the performance of school transport that is currently running, to analyze route changes, and to calculate the BOK (Vehicle Operating Costs) needed for the 2019 school year. This research uses primary data and secondary data. Primary data uses the form of interviews, questionnaires from students' routes, headway surveys and load factors. Secondary data uses the form of fleets, routes and existing routes, and route lengths. The method which is used is the analysis method based on the data obtained. The method is analyzing the performance of Gianyar Regency school transport according to the provisions of the Department of Transportation, arranging transportation routes, and calculating the vehicle operational costs. The results of Gianyar Regency school transport performance evaluation currently show the number of passengers, travel distance and transportation waiting time because they did not meet the standards of Department of Transportation, the level of fuel consumption with 12 routes that meet the standards, load factors only 10 routes that meet the standards, travel time only 1 route that meets the standards, travel speeds of all routes meet the standard, and headways with 5 routes that meet the standards. The results of the need analysis to change the route for 2019 are planned to be come 29 routes for Trans Gianyar transportation and 12 routes for the Trans Harmoni Bus. The highest BOK (Vehicle Operating Costs) per year and per kilometer based on the route plan for public passenger car vehicles is Rp. 67,218,681 per year and Rp. 14,142 per KM, for small bus vehicles Rp. 66,366,399 per year and Rp. 14,417 per km, and for bus vehicles medium amounting to Rp. 208,254,660 per year and Rp. 26,885 per KM.